2012
DOI: 10.1016/j.devcel.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of PINK1 Binding to the TOM Complex and Alternate Intracellular Membranes in Recruitment and Activation of the E3 Ligase Parkin

Abstract: Summary Mutations in the mitochondrial kinase PINK1 and the cytosolic E3 ligase Parkin can cause Parkinson’s disease. Damaged mitochondria accumulate PINK1 on the outer membrane where, dependent on kinase activity, it recruits and activates Parkin to induce mitophagy, potentially maintaining organelle fidelity. How PINK1 recruits Parkin is unknown. We show that endogenous PINK1 forms a 700 kDa complex with the translocase of the outer membrane (TOM) selectively on depolarized mitochondria whereas PINK1 ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
527
4
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(565 citation statements)
references
References 54 publications
31
527
4
3
Order By: Relevance
“…Presumably, as a kinase, Pink1 can phosphorylate some mitochondrial surface proteins or itself serve as an anchor for Parkin. The possibility that there are unique mitochondrial anchors has been ruled out by a recent study: when Pink1 is ectopically targeted to peroxisomes, Parkin is redirected to peroxisomes and, interestingly, it induces their autophagy [21]. In line with this observation, Pink1 has been shown to interact with Parkin [22].…”
Section: Introductionsupporting
confidence: 59%
“…Presumably, as a kinase, Pink1 can phosphorylate some mitochondrial surface proteins or itself serve as an anchor for Parkin. The possibility that there are unique mitochondrial anchors has been ruled out by a recent study: when Pink1 is ectopically targeted to peroxisomes, Parkin is redirected to peroxisomes and, interestingly, it induces their autophagy [21]. In line with this observation, Pink1 has been shown to interact with Parkin [22].…”
Section: Introductionsupporting
confidence: 59%
“…We have recently identified Mtx2 and 1 as receptors for Bak during TNFα/CHX induced apoptosis (6). Quite interestingly, recent results have shown that TOM machinery is essential in the mitochondrial elimination during autophagy by controlling the PINK-PARK pathway (25,26). These results confirm that mitochondrial protein import machineries are implicated in cell survival not only through regulation of metabolism but also though the control of cell death programs.…”
Section: Discussionsupporting
confidence: 69%
“…[70][71][72][73] Loss of mitochondrial membrane potential may be the event that acutely activates this pathway; loss of the potential gradient precludes import of PINK1 to the inner membrane, thereby stabilizing intact PINK1 on the mitochondrial outer membrane where it interacts with the TOM complex. 74 In this manner, PINK1 serves as a sensor for mitochondrial damage. Accumulation of PINK1 on the mitochondrial surface induces translocation of Parkin from the cytosol to damaged mitochondria through a mechanism as yet unknown.…”
Section: The Pink1/parkin Pathway Of Mitophagymentioning
confidence: 99%
“…This hypothesis is consistent with the ability of Parkin ectopically targeted to peroxisomes to mediate surface ubiquitination and autophagic degradation of these organelles. 74 In summary, while the ubiquitin ligase activity of Parkin is well established, further work is required to determine how Parkin-mediated ubiquitination promotes mitophagy.…”
Section: Parkin Promotes Ubiquitination Of Mitochondrial Proteinsmentioning
confidence: 99%
See 1 more Smart Citation